Review Paper on Penetrating Brain Injury: Ethical Quandaries in the Trauma Bay and Beyond. Issue 1 (23rd January 2023) - Zakrison, Tanya L.; Essig, Rachael; Polcari, Ann; McKinley, William; Arnold, Damon; Beyene, Robel; Wilson, Kenneth; Rogers, Selwyn; Matthews, Jeffrey B.; Millis, J. Michael; Angelos, Peter; O'Connor, Michael; et al.
Abstract : Objective: The aim of this review was to review the ethical and multidisciplinary clinical challenges facing trauma surgeons when resuscitating patients presenting with penetrating brain injury (PBI) and multicavitary trauma. Background: While there is a significant gap in the literature on managing PBI in patients presenting with multisystem trauma, recent data demonstrate that resuscitation and prognostic features for such patients remains poorly described, with trauma guidelines out of date in this field. Methods: We reviewed a combination of recent multidisciplinary evidence-informed guidelines for PBI and coupled this with expert opinion from trauma, neurosurgery, neurocritical care, pediatric and transplant surgery, surgical ethics and importantly our community partners. Results: Traditional prognostic signs utilized in traumatic brain injury may not be applicable to PBI with a multidisciplinary team approach suggested on a case-by-case basis. Even with no role for neurosurgical intervention, neurocritical care, and neurointerventional support may be warranted, in parallel to multicavitary operative intervention. Special considerations should be afforded for pediatric PBI. Ethical considerations center on providing the patient with the best chance of survival. Consideration of organ donation should be considered as part of the continuum of patient, proxy and family-centric support and care. Community input is crucial in guiding decision making or protocol establishment on an institutional level. Conclusions: Support of the patient after multicavitary PBI can be complex and is best addressed in a multidisciplinary fashion with extensive community involvement.